Sumber dan Media Pembelajaran Anak Usia Dini di TK Fatma School Pancut Batu - Oktavia, Cindi; Zahra Lubis, Hilda (Al Athfal : Jurnal Kajian Perkembangan Anak dan Manajemen Pendidikan Usia Dini, 2023)
This research is related to early childhood learning resources and media at Fatma school kindergarten, while the purpose of this research is to find out the problems of the unavailability of learning resources and media in the kindergarten. The research method used is descriptive qualitative method with data collection techniques used are observation, interview, and documentation techniques. The results of this study indicate that the problem of learning resources and media in Farma school kindergarten is indicated by the lack of media so that young children are bored and bored in learning. For this reason, this research is expected for the reader writer to be able to help and facilitate the school.